ULTRASOUND AS FIRST LINE STEP IN ANAEMIA DIAGNOSTICS - chiara mozzini; giancarlo pesce; alder casadei; domenico girelli; maurizio soresi (Mediterranean Journal of Hematology and Infectious Diseases)
This review covers the role of ultrasonography as an essential non-invasive diagnostic approach when facing patients with anemia, a common clinical problem. Abdomen ultrasound is well recognized as a first-line examination in the setting of blood loss, both acute and chronic. Less is clear about the additional opportunities, given by ultrasound in anemia, due to the many other possible causes.